Extended Spectrum ß-Lactamase Producing Escherichia coli from Bagmati River Water: a Threat of Spread of Resistant Bacterial Infection to Human - Niroula, Mandira; Banjara, Megha Raj (Journal of Institute of Science and Technology, 2024)
Aquatic environments can be the sources for the spread of antibiotic-resistant microorganisms and resistance genes. Escherichia coli is one of the bacteria taken as an indicator of water contamination with human faecal matter. CTX-M producing E. coli is the most common type of extended-spectrum ß- lactamase (ESBL) producing E. coli worldwide. This study was conducted from October 2019 to December 2020 to determine the proportion of CTX-M gene among ESBL E. coli isolated from the Bagmati River. Thirty-nine water samples in triplicates were collected from 13 different points of Bagmati River in Kathmandu Valley and analyzed for isolation of E. coli. Antimicrobial susceptibility test was performed by modified Kirby- Bauer disc diffusion method. ESBL was confirmed phenotypically by the combination disk method recommended by CLSI guidelines. Alkaline hydrolysis method was used for plasmid DNA extraction and CTX-M gene was detected by a polymerase chain reaction and agarose gel electrophoresis. E. coli was isolated from 76.9% (n= 30) samples and 80% (n= 24) of E. coli isolates were multidrug-resistant (MDR). Out of 24 MDR E. coli, 33.3% (n= 10) were ESBL producers. Among 10 ESBL E. coli, 70% (n= 7) had CTX-M gene. It shows that Bagmati River water is polluted due to anthropogenic activities. The resistant bacteria may circulate from water to the community posing a potential threat of infection. Effective treatment of river water is recommended to prevent the spread of antibiotic-resistant microorganisms.